2017
DOI: 10.1007/s00134-017-4750-z
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges in the management of sepsis in ICUs in resource-poor settings and suggestions for the future

Abstract: Background: Sepsis is a major reason for intensive care unit (ICU) admission, also in resource-poor settings. ICUs in low-and middle-income countries (LMICs) face many challenges that could affect patient outcome. Aim: To describe differences between resource-poor and resource-rich settings regarding the epidemiology, pathophysiology, economics and research aspects of sepsis. We restricted this manuscript to the ICU setting even knowing that many sepsis patients in LMICs are treated outside an ICU. Findings: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
138
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 94 publications
(135 reference statements)
2
138
0
Order By: Relevance
“…This should be at 5 L/min to reach SpO 2 targets of ≥90% in non-pregnant adults and children, and ≥92-95% in pregnant women [30][31][32]. In the absence of shock, intravenous fluids should be carefully administered [33]. Renal replacement therapy (RRT) should be initiated for patients with an AKI.…”
Section: Treatmentmentioning
confidence: 99%
“…This should be at 5 L/min to reach SpO 2 targets of ≥90% in non-pregnant adults and children, and ≥92-95% in pregnant women [30][31][32]. In the absence of shock, intravenous fluids should be carefully administered [33]. Renal replacement therapy (RRT) should be initiated for patients with an AKI.…”
Section: Treatmentmentioning
confidence: 99%
“…However, trials of fluid resuscitation in sepsis in sub-Saharan Africa showed increased mortality in children [46] and adults [47,48] illustrating the challenges of applying well-accepted resuscitation algorithms from resource-rich settings (that assume mechanical ventilation availability and intensive care capacity) in resource-limited settings. Defining safe fluid resuscitation approaches for resource-limited settings is a major research priority and reinforces the need for clinical trials that include rules for stopping therapy and that minimize risk of adverse effects by integrating local ICU practices [86].…”
Section: The Rwanda Human Resources For Health (Hrh) Program: a Partnmentioning
confidence: 99%
“…around the world differ in available resources, and our working group [2] and others [1] have different definitions what an ICU entails. In this chapter, we aim to answer seven questions basic prerequisites for quality intensive care in resource-limited settings: (1) Which healthcare professionals should provide care in ICUs in resourcelimited settings?…”
mentioning
confidence: 99%